Pendampingan UMKM Masyarakat dengan Program Pembuatan Spanduk/Banner yang Sesuai dengan Kaidah Bahasa Indonesia di Lingkungan Jl. Telaga Dewa 4 RT 50/RW 04 Kota Bengkulu (HORIZON: Indonesian Journal of Multidisciplinary, 2026)
Micro, Small, and Medium Enterprises (MSMEs) play a strategic role in driving the regional economy and creating jobs. However, at the business level, banners, and logos are often used without regard to Indonesian language rules and the basic principles of visual communication design, potentially reducing the credibility and effectiveness of business promotions. This community service activity aims to improve the linguistic literacy and simple design skills of MSMEs through mentoring in the preparation of visual identities that comply with the General Guidelines for Indonesian Spelling and basic typography principles. The method used is a community-based participatory research approach with stages of needs identification, socialization, technical assistance, and evaluation of results. The activity was carried out with MSMEs in the area of ​​Jl. Telaga Dewa 4, RT 50, RW 04. The results of the community service showed an increase in participants' understanding of the correct use of Indonesian in promotional media, as well as the creation of banners, banners, and business logos that are more communicative, consistent, and operationally feasible. This program contributes to strengthening the visual identity of MSMEs while supporting the improvement of the quality of marketing communications at the local level.